Are current mental health assessment formats consistent with contemporary thinking and practice?. (9th September 2019) - Wand, Timothy; Buchanan‐Hagen, Sally; Derrick, Kate; Harris, Michelle
Abstract: Conducting and documenting a mental health assessment is considered a central activity from a clinical and organizational perspective. In recent years, thinking and practice in mental health service delivery has changed considerably to embrace principles of recovery, trauma‐informed care, and strengths‐based approaches. The aim of the present study was to determine the degree to which these concepts are reflected in the content of assessment formats across mental health services in Australia and New Zealand. Copies of mental health assessments used in each state and territory in Australia, and three District Health Boards in New Zealand were obtained. Assessment formats were compared for similarities and differences, and to determine whether concepts of recovery, trauma‐informed care, and strengths‐based approaches were incorporated. The assessment formats analysed ( n = 11) contained many traditional features targeted at identifying harms, problems, risks, and pathology. Some attempts to redress this discrepancy were evident. Overall, assessment formats did not adequately voice the individual's perspective or promote a truly comprehensive assessment through an exploration of individual strengths, skills and abilities, past successes, and future hopes. Assessment formats across Australia and New Zealand are not currently aligned with contemporary thinking and practice in mental health care. Given the heavy influence that mental health assessment has on clinical decision making in particular, a reappraisal of the focus and content of formats used is urgently required.